Oral cancer awareness, knowledge, and practices among Saudi general dentists - Zayed Ali Assiri; Abdulrahman Ahmed Alshehri; Alia Khalid Alfadhel (Wolters Kluwer Medknow Publications, 2019)
Objectives: The present study aimed to investigate oral cancer (OC) awareness, knowledge, and practices among Saudi general dentists. Materials and Methods: We included dentists who were recognized and licensed by the Saudi Commission for Health Specialties. They were e-mailed officially with a 28-item questionnaire and constructed to investigate the study objectives. Results: The final sample included 326 dentists. About 85.6% of the participants reported their awareness; this was confirmed when similar percentage (87.4%) stated that there are etiological factors other than tobacco and alcohol for OC. Only 34.7% of the participants had sufficient knowledge concerning the prevention and detection of OC. Concerning the referral, 53.4% referred their patients to oral medicine specialist. Conclusions: Our findings revealed that chances exist to improve the knowledge, increase awareness, and develop right practices toward OC. Furthermore, our results revealed that dentists believed their knowledge was insufficient to detect OCs, although most of them showed reasonable level of knowledge about some aspects of diagnosing OCs. All these emphasize general dentists' role in the prevention and diagnosis and the need to improve dentists' knowledge and practices toward OC.